Profiles and characteristics of bronchial responsiveness in general 7‐year‐old children. Issue 6 (11th March 2019) - Park, Ji Soo; Choi, Yun Jung; Suh, Dong In; Jung, Sungsu; Kim, Young‐Ho; Lee, So‐Yeon; Yang, Song‐I; Kwon, Ji‐Won; Jang, Gwang Cheon; Sun, Yong Han; Woo, Sung‐Il; Youn, You‐Sook; et al.
Abstract: Background: Although bronchial responsiveness (BR) is usually categorized as normal or hyperresponsive to aid the diagnosis of asthma, it exists on a continuous spectrum, not in a dichotomous manner. We aimed to evaluate the distribution profile of BR in a general population of 7‐year‐olds. Methods: In 2015, 7‐year‐old Korean children from a nationwide birth cohort study visited regional study hospitals for skin prick test, standard spirometry, and bronchial provocation to establish reference values for the general population. Their BR degrees were categorized into five ordered groups: hyperresponsive BRs were classified into group 1 (provocative concentration (PC) of methacholine causing a 20% fall in forced expiratory volume in 1 second [FEV1], PC20 of <4 mg/mL) and group 2 (PC20 of ≥4 mg/mL and <16 mg/mL), and nonresponsive BRs were categorized into group 3 (final FEV1 percentage fall after inhaling 16 mg/mL of methacholine [FEV1%fall] of >15% and ≤20%), group 4 (FEV1%fall of >10% and ≤15%), and group 5 (FEV1%fall of ≤10%). Results: In total, 559 subjects finished all tests reliably. Groups 1 and 2 comprised 10.0% and 15.7% of the total population, respectively. Groups 3, 4, and 5 comprised 14.7%, 18.4%, and 41.1%, respectively. As the group number increased, the proportion of those with recent wheezing and those with indoor allergen sensitization decreased ( P for trend = 0.001 and P for trend < 0.001, respectively), and the baseline FEV1/FVC increased ( P for trend < 0.001) Conclusion: BR of the 7‐year‐olds in the general population, while showing a wide distribution across phenotypes, is associated with allergic symptoms, negatively correlated with baseline lung function and positively correlated with indoor allergen sensitization.